The The Concept of Profit Sharing Agreement in Land Management in Segara Kodang, Sesetan Village, South Denpasar District, Denpasar City - UTAMA, Kartika Jaya; SUKANDIA, I Nyoman; AGUNG, Anak Agung Istri; DEWI, Ida Ayu Permata Winditya; YUDHA, I Putu Wira Dharma Putra (Protection: Journal Of Land And Environmental Law, 2024)
The importance of the meaning of soil for human life is because human life is utterly inseparable from the soil. They live on the land and obtain food by utilizing the land. The amount of land that can be controlled by humans can be reduced due to erosion, while the number of people who wish for land is constantly increasing. In answering legal problems, this research uses an empirical method.   The people of Sesetan Village use customary Law passed down from generation to generation, carried out orally based on trust and agreement, and no deed is made from these legal acts. The implementation of the profit-sharing agreement can be carried out well with the existence of a trust system between the customary village institution and the community in maintaining the agreement as well as knowing and implementing their respective rights and obligations agreed upon at the time of making the agreement which aims to improve the economy of the community in the use of village land and especially the customary Village itself.